The Impact of Anxiety on Academic Procrastination Among University Students in Indonesia - Fernanda, Felicia; Lidiawati, Krishervina Rani (Universitas Pendidikan Mandalika, 2025)
This study aims to explore the influence of anxiety on academic procrastination across university students in Indonesia, measuring both state and trait anxiety. The research used a quantitative approach with correlational design. A total of 559 university students in Indonesia participated in this study. The measurement tools employed were the STAI-5 for anxiety and the PASS for academic procrastination. Data analysis using multiple linear regression tests showed a significant influence of anxiety on academic procrastination, accounting for 14.1% of the variance. A significant positive relationship was found between state anxiety and academic procrastination. Additionally, this study identified a significant positive relationship between trait anxiety and academic procrastination. This study found that female university students had higher levels of both state anxiety and trait anxiety compared to male university students. Additionally, the research discovered that university students who participated in organizations tend to have lower levels of academic procrastination than those who did not. Furthermore, academic procrastination was significantly different when analyzed by academic year.